(untitled) (Jahangirnagar University Journal of Biological Sciences, 2025)
Colouring agents (CAs) are frequently utilized by food and pharmaceutical manufacturers to enhance the visual appeal of products, imparting consumer preference and product identification. However, concerns have been raised regarding their potential toxicity and health effects. This review broadly outlines the toxicity profiles and potential health benefits of using different CAs in foods and pharmaceutical products. This work was carried out using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 protocol, comprising 54 articles. Here we discuss different CAs such as Allura Red, Amaranth, Ponceau, Tartrazine, Sunset Yellow, Erythrosine, Brilliant Blue, Patent Blue, Curcumin, Saffron, and Carotenoids. For foods and pharmaceutical products, we individually categorized the benefits and toxicities of these CAs. Besides the health benefits of colour additives, this review highlights numerous toxicities with immediate-to long-term effects on the liver, kidney, brain, lipid profile, immune system, reproductive system, genotoxicity, oxidative stress biomarkers, and cancer. Furthermore, the development and use of safer and more efficient Colourants for food and pharmaceuticals, along with emerging trends and directions in these fields, were addressed. This review will aid in clarifying the intricate relationship between CAs and human health to direct future studies and local regulatory actions. Jahangirnagar University J. Biol. Sci. 13(1 & 2): 23-39, 2024 (June & December)